(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
More female participation was acknowledged by the development community to be essential toachieving the goal of sanitation for everyone during the International Drinking Water Supply and SanitationDecade (1981–90). The United Nations system and bilateral organisations have started new projects aimedat women in an effort to increase their participation in the development of water supply and sanitationservices. Water, sanitation, and health are often women’s responsibilities. As women have traditionallybeen the ones who collect water, teach cleanliness to children, and understand the health consequencesof unsanitary living conditions, they have always held a disproportionate amount of environmentalknowledge. Unlike males, who are seldom forced to go large distances to gather water, women and girlsare disproportionately asked to do so (WGTF, 2006). As a result, this study has made a serious effort toinquire into the worth of women’s participation in sanitation-related efforts.